High technology small and medium sized enterprises (HTSMEs) : an assessment of the determinants of growth and constraints faced by HTSMEs in Malaysia - Mohd. Osman, Mohd. Hassan (2002)
The industrial development of Malaysia has moved towards capital-intensive, high technology and high value-added industries. The development of high technology industries is an important element in the country's industrialisation process. High technology small and medium-sized enterprises (HTSMEs) are considered a key feature of growth in the high technology sphere in Malaysia - the creation and development of indigenous HTSMEs is vital. The primary aim of this research is to examine the growth of HTSMEs and provide policy makers, owner-managers (OMS) and academics with a greater understanding of the factors affecting the growth of such firms in Malaysia. This study also identifies the main constraints faced by HTSMEs and explores ways in which these constraints might be overcome. The programme of research builds upon past studies, but it adds to existing knowledge in an area that is ripe for research. After a literature review, and the development of an overarching theoretical framework, a number of hypotheses are put forward. The methodological approach combines a questionnaire survey with case studies based on interviews with selected HTSMEs and key informants. The questionnaire is principally concerned with identifying the factors that contribute to growth in HTSMEs, whereas the case studies and interviews concentrate on exploring the constraints identified in the questionnaire survey. The questionnaires were distributed to firms in databases maintained by a number of Government bodies. All the sample firms are considered high technology, as defined by the Promotion of Investment Act 1986. The sample includes firms involved in a variety of activities, from the manufacture of high technology products to the processing of resource-based products. Firms were randomly selected to reflect the size and racial composition of firms in the underlying population of HTSMEs. The questionnaire data were supplemented by 15 in-depth case studies. Two major findings emerge from this study. First, a number of determinants did have a significant effect on growth of HTSMEs: age of OM; age and size of firm; process innovation and R&D. However, most the hypotheses relating to business strategy were rejected; the researcher offers some explanations for these rejections. Second, the case studies demonstrate that labour constraints among HTSMEs are prevalent, whereas other propositions were not substantiated. In particular, the case studies raise a number of questions about the effectiveness of Government support programmes. On the basis of the research findings, the researcher is able to put forward a series of recommendations to enhance the growth of HTSMEs in Malaysia.